Faktor Risiko Tuberkulosis Paru Pada Warga Binaan Pemasyarakatan di Lembaga Pemasyarakatan Kelas I Semarang - Evrilda Andani Putri; Martini Martini; Lintang Dian Saraswati; Mateus Sakundarno adi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Backgound: Tuberculosis (TB) is a chronic granulomatous infection caused by Mycobacterium tuberculosis. One of the risk populations are prisoners in the prisons. Prevalence rate of tuberculosis in the prisons was known to be 3 times higher than in the general population. Prevalence of tuberculosis on prisoners in Prison Class I Semarang was 1,51% (2015), and increased to 15,12% (2016).But there’s no data about the risk factor of pulmonary tuberculosis. This study aims to analyze the risk factors of pulmonary tuberculosis on prisoners in Prison Class I Semarang.Methods: This study is an analytic observasional study with case control approach. This research subject is prisoners which is suffering TB as case and not suffering TB as control. In this research are 76 from 38 cases and 38 controls. The selection case sample with population total study, and control sample withquota sampling.Result: The level of lighting (OR=4,956;95%CI=1,452-16,928; p=0,015); coughing behavior (OR=3,927;95%CI=1,288-8,440;p=0,022)is associated with pulmonary tuberculosis. The histories of same bedding patients (p=0,227); long lived in the prison (p=0,251); existence of the bengker (p=0,062); smoking status (p=0,608); the humidity level (p=>0,999); spuntum disposal behavior (p=0,481) werenot related to the incidence of pulmonary tuberculosis.Conclusion: In this study, level of lighting is the most risk factor of pulmonary tuberculosis incidence on prisoners in Prison Class I Semarang.